Literature Riview: Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar dan Sikap Ilmiah Siswa - Linda Kurnia; Tri Ariani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The purpose of this article is to thoroughly examine and summarize the findings of various studies on how to develop inquiry-based Student Worksheets (LKPD). In addition, this study also aims to determine the effectiveness of LKPD in improving learning outcomes and shaping students' scientific attitudes. The studies analyzed include several types of research approaches, namely Research and Development (R&D) focusing on product validity and feasibility, Classroom Action Research (CAR), and Quasi-Experiments. All of these studies share a common focus, namely applying a guided inquiry model or LKPD, in which students are guided to discover concepts on their own. The subjects reviewed were students from elementary school (SD), junior high school (SMP), to senior high school (SMA) in science subjects. The findings from this review show that guided inquiry worksheets are consistently declared feasible and practical for use, according to reports from R&D studies. Empirically, the application of LKPD or guided inquiry models has been proven to have a significant and positive impact on students' academic scores and scientific attitude development at various levels. The average increase in learning outcomes, as measured by N-gain scores, is generally in the moderate to high category. Significant improvements are also seen in other abilities, such as scientific process skills and scientific attitudes.